Evaluation of morphometric parameters and erosion status in Burdur Lake Watershed - Ahmet Alper Babalık; İbrahim Dursun (Turkish Journal of Forestry, 2023)
The research was carried out to determine the morphometric analysis parameters of the Burdur Lake Watershed. In addition, the erosion situation in the watershed has been evaluated with the help of morphometric parameters. The data basis of the research was created using the Digital Elevation Model (DEM) obtained from Shuttle Radar Topography Mission (SRTM). The determination of the stream indexes used in the analyzes was made via the ArcGIS 10.2 program. In this context; When the morphometric analysis results of the parameters of the linear, areal and relief morphometries of the watershed are examined; bifurcation ratio 3.42, stream length ratio 3.46, drainage density 1.25, stream frequency 0.95, form factor 0.25, gravelius index 2.66, circularity ratio 0.14, elongation ratio 0.28, basin relief 1534, relief ratio 0.013, relative relief 0.29, ruggedness number respectively 1.92 and the hypsometric integral value was found to be 0.28. In general, it has been found that the infiltration capacity of the watershed is high, stream frequency and flood sensitivity are low. In consequence of morphometric analysis, it was determined that the area had arid climatic conditions and weak vegetation. As a result, it has been concluded that the erosion risk is relatively low in most of morphometry parameters. According to these results, it can be said that morphometric analysis are an important tool for interpreting the erosion situation in the watershed.